Regional Determinant in Critics of Stylized Approaches to Tax Incentives of Investment Activity in Russia. - Viktor V. IVANOV; Neli R. ABRAMISHVILI; Nadezhda A. LVOVA; Natalia V. POKROVSKAIA; Alexander Yu. Andrianov (Communications of International Proceedings, 2020)
The paper is devoted to discussing stylized approaches to tax incentives through the research of investment behavior in Russian regions. A review of research on the investment determinants made it possible to divide the influence on the investment process of companies, financial market and state policy. The empirical research was based on the socio-economic characteristics of Russia in the regional context. Based on the analysis of investment activity in the Northern regions of Russia, it was proved that companies operating in these regions especially need constant and timely updating of equipment as well as the volume of investment is insufficient and the lack of proper attention to this issue leads to the sharp deterioration of heavy working conditions in the region. It was substantiated that national specific of economy and investment behavior in Russia result in the need for a differentiated approach to investment tax incentives. The study was carried out with the financial support of the Russian Foundation for Basic Research within the framework of scientific project No. 19-010-00198.
Keywords: investments; investment activity; investment activity of Russian enterprises; tax incentives of investment activity; financial system.